Conservative treatment of the longitudinal flatfeet in children - Shulga, O. (Journal of Education, Health and Sport, 2021)
Introduction. A significant percentage of the musculoskeletal system pathology in children is currently fall on the foot pathology – longitudinal flatfeet, which is not only a medical, but also a social problem. The incidence of this pathology is up to 58% of the total orthopedic foot pathology. Traditional methods of treatment and prevention of mild (I– II severity) longitudinal flatfeet (LF), which are known today (massage, physiotherapy exercises, the use of orthopedic devices, electromyostimulation) do not give a significant effect and a stable, long-term result. This makes us look for more effective methods of conservative treatment of LF of the I– II severity degree, which have a pathogenic orientation and physiological effect. Purpose of the work: to develop the most effective algorithm for the complex conservative treatment of LF, depending on the severity, hemodynamic disorders, deformity options, foot rigidity. Materials and methods. Conservative treatment was carried out in 62 patients aged 10– 18 years with LF of the I– II severity degree. Depending on the clinical manifestations and examination results, the treatment was carried out in two stages. At the first stage, serial casting was used (in the presence of concomitant deformations – silicone pelottes were used). Results. The results of the two-stage conservative treatment of LF demonstrate the effectiveness of serial casting in combination with the use of silicone pelottes and biostimulators in comparison with traditional methods of foot correction. Conclusions. Algorithms for conservative treatment of LF were developed, depending on the severity, nature of the deformity, hemodynamic disorders and muscle tone of the lower leg and foot.